Efecto de dos niveles de suplementación sobre la respuesta productiva de llamas (Lama glama) en pastoreo = Effect of two levels of supplementation on the productive response of llamas (Lama glama) in grazing - Labarta, Fernando Eduardo (2022)
The aim of this study was to evaluate de productive response to supplementation with concentrate in the diet of llamas (Lama glama) on natural grasslands. Two fattening trials were carried out, in consecutive years, with 18 whole male llamas. In the first, a supplementation of 1.5% was used and in the second, 2%, of the group's average live weight on a dry basis. The group of animals that did not receive supplementation was considered as a control treatment and was assigned only to direct grazing of the lots, which were made up of natural grasslands. The supplement consisted of 80% corn grain and 20% soybean expeller. It was offered ground in a daily delivery in group form, in the morning. A randomized complete block experimental design was used. The first trial lasted 34 days, the second 60 days, with a 10-day adaptation period. In both trials, the parameters associated with the productive response (final weight, final fast weight, daily live weight gain, body condition score) showed statistically significant differences (p <0.05), but not in initial weight (p> 0.1). Regarding the parameters related to carcass characteristics and quality, statistically significant differences (p <0.05) were observed in the two tests for cold carcass weight, carcass yield, and carcass compactness index, but they showed significant differences only in the second trial for back fat thickness, perirenal fat, fat content extracted and weighed in palpation areas. These results would indicate that the llamas fattened with native grass pasture and supplemented with concentrates improved the productive parameters and the parameters related to the characteristics and quality of the carcasses.